Development of mobile application to report criminal acts in young areas of Peru - Meneses Claudio, Brian Andreé (2023)
This research work entitled "Design of a mobile application for complaints in real time to the national police", being that the police officer must be in his office or in front of a computer with an Internet connection so that he can see the complaints that are in charge, or manually search for documents, cases, folders.For this reason, a mobile application called "mobile application" was proposed and developed; as a solution proposal. Its purpose is to solve different problems without having to be in the police station and / or in the office. We want to help the population to carry out any complaint in a more EASY AND QUICK way, and this will be achieved through the application "MOBILE APPLICATION", with Android operating system, resulting in a friendly and easy-to-use mobile complaint management application.For the present project, XP Extreme Programming (eXtreme programming) methodology was used, which adapts to the necessary characteristics required for the application to have optimal performance, in addition to facilitating the development and design work of the application. We made use of a series of technologies and tools for the development and design work of the application, we will use IDE (integrated development environment) Android Studio that provides us with comprehensive services, which facilitates the task in time of programming our mobile application.